Preference, Knowledge, and Attitudes of Parents Toward Cognitive Behavioral Therapy for Their Children in Riyadh, Saudi Arabia - Alenezi, Shuliweeh; Albawardi, Ibrahim M.; Aldakhilallah, Amirah; Alnufaei, Ghaliah S.; Alshabri, Rahaf; Alhamid, Lama; Alotaiby, Alanoud; Alharbi, Norah (Frontiers in Psychology, 2021)
Introduction: Cognitive behavioral therapy (CBT) for children and adolescents has shown efficacy in treating different psychiatric disorders. It has been added to multiple clinical guidelines as the first-line treatment. However, despite more studies of its efficacy, CBT is underutilized in clinical settings due to a lack of rigorous training programs and qualified CBT therapists. The limited knowledge of parents in this intervention and their negative attitudes toward it have been considered as possible reasons. Methods: This is a cross-sectional survey-based study among 464 Saudi parents living in Riyadh city. We aimed to evaluate the preference, knowledge, and attitudes of Saudi parents toward CBT for their children. We compared the difference in the level of knowledge and attitudes toward CBT in relation to the characteristics of parents. An online questionnaire that included 39 questions was carefully reconstructed from four validated scales, approved by an expert panel, and piloted. Participants were recruited to participate through online social media. Results: Saudi parents had average knowledge about CBT; however, they had positive attitudes toward the therapy itself and its role in treating the behavioral issues of children. Male participants showed better knowledge than female participants. Participants with higher education and those with high income had more favorable attitudes toward CBT than others. Conclusion: The knowledge of parents is considered inadequate and indicated the need for more awareness and perhaps mass education. In contrast, they maintained positive attitudes and were interested in evidence-based treatment, with more preference toward non-psychopharmacological interventions.